2017
DOI: 10.1016/j.acalib.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Will Web Search Engines Replace Bibliographic Databases in the Systematic Identification of Research?

Abstract: Will web search engines replace bibliographic databases in the systematic identification of research? AbstractThe availability of web search engines provides opportunities in addition to those provided by bibliographic databases for identifying academic literature, but their usefulness for retrieving research is uncertain. A rigorous literature search was undertaken to investigate whether web search engines might replace bibliographic databases, using empirical research in health and social care as a case stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Academic librarians frequently guide library users in their quest for relevant information materials. As the quantity of available information continues to grow, the task of retrieving relevant information becomes more and more challenging [19]. Academic libraries all over the world are experiencing a paradigm shift in acquiring, storing and retrieving information, because of the application of information communication technologies (ICTs).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Academic librarians frequently guide library users in their quest for relevant information materials. As the quantity of available information continues to grow, the task of retrieving relevant information becomes more and more challenging [19]. Academic libraries all over the world are experiencing a paradigm shift in acquiring, storing and retrieving information, because of the application of information communication technologies (ICTs).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The metadata sets of the publications registered in the databases are not standardized. It is common to have multiple versions of the same publication [15,16]. In addition, authors of publications may inadvertently "obscure" their articles by using loosely related popular terms in the titles and keywords, decreasing the specificity of articles to increase the likelihood of the article being indexed in and prioritized by the query engines, as titles play an essential role in making publications accessible to search engines and attractive to users [17].…”
Section: Current Challenges In Systematic Review and Map Sectormentioning
confidence: 99%
“…For example, there are very few available PubMed MeSH search terms to filter searches on this extensive database. Bates et al (2017) found in a systematic review that web search engines were not as effective as were bibliographic databases in aiding the location of academic publications. While they did not specify whether they sought a particular research methodology (i.e.…”
Section: The Challenges Of Searching For Qualitative Reportsmentioning
confidence: 99%